Islam in Europe - Islamic Foundation (Leicester : The Islamic Foundation, 1993)
Islam in Europe video brings together a host of Muslim scholars drawn from different parts of the world, especially Europe, delibrating on the role of Islam in Europe.
A documentary video encapsulating the one-day international conference organized by the Islamic Foundation on 5th September, 1992.
Copy available in DVD format.
Keywords: Islam -- Europe -- Congresses